INTEGRASI SENI UKIR (UKIRAN) TORAJA DALAM PEMBELAJARAN SBDP KELAS IV DI UPT SDN 10 MAKALE - Parerungan, Noprianto; Padallingan, Yohanes; Kabanga`, Theresyam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the integration of Torajan wood carving into Arts, Culture, and Crafts (SBDP) learning for fourth-grade students at UPT SDN 10 Makale and to identify the improvement of students' understanding and artistic skills after implementing local culture-based learning. This study employed a qualitative approach with a descriptive qualitative research design. The research participants consisted of the fourth-grade teacher and fourth-grade students of UPT SDN 10 Makale. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicated that the integration of Torajan wood carving into SBDP learning was implemented through the introduction of the Pa'Barana', Pa'Manuk, and Pa'Sussuk motifs, direct observation of Torajan carvings in the surrounding environment, discussions of their philosophical meanings, and practice in drawing decorative patterns. The use of local cultural elements in the learning process improved students' understanding of visual art elements, enhanced their skills in creating decorative patterns, and fostered pride and appreciation for Torajan cultural heritage. Although several challenges were encountered, including limited learning media and students' initial understanding of Torajan carving motifs, these obstacles were addressed by utilizing the surrounding environment as a learning resource and providing relevant visual examples. Therefore, the integration of Torajan wood carving into SBDP learning serves as a contextual and meaningful learning approach while supporting the preservation of local culture from the elementary school level.